2019
DOI: 10.1002/mrm.27744
|View full text |Cite
|
Sign up to set email alerts
|

3D‐multi‐spectral T2 mapping near metal implants

Abstract: Purpose Due to host‐mediated adverse reaction to metallic debris, there is an increasing need for noninvasive assessment of the soft tissue surrounding large joint arthroplasties. Quantitative T2 mapping can be beneficial for tissue characterization and early diagnosis of tissue pathology but current T2 mapping techniques lack the capability to image near metal hardware. A novel multi‐spectral T2 mapping technique is proposed to address this unmet need. Methods A T2 mapping pulse sequence based on routinely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Finally, only 2 TEs, 9.8 and 90 ms, were used for T2 calculation and it is possible that these TEs may be too short for to characterize long T2 species within soft tissue structures. A prior study found that capping values at 250 ms would minimize error in the resulting summary statistics, 23 which was utilized in a prior study, 22 as well as the current study. We found that 14 of our 28 subjects had voxels with T2 > 250 ms present, in which these voxels represented only a small percentage (4.4 ± 5.4%) of the IPFP volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, only 2 TEs, 9.8 and 90 ms, were used for T2 calculation and it is possible that these TEs may be too short for to characterize long T2 species within soft tissue structures. A prior study found that capping values at 250 ms would minimize error in the resulting summary statistics, 23 which was utilized in a prior study, 22 as well as the current study. We found that 14 of our 28 subjects had voxels with T2 > 250 ms present, in which these voxels represented only a small percentage (4.4 ± 5.4%) of the IPFP volume.…”
Section: Discussionmentioning
confidence: 99%
“…T2=TE2TE1ln(SI1)ln(SI2) ${{\rm{T}}}_{2}=\frac{{\mathrm{TE}}_{2}-{\mathrm{TE}}_{1}}{\mathrm{ln}({\mathrm{SI}}_{1})-\mathrm{ln}({\mathrm{SI}}_{2})}$where TE 1 and TE 2 are the times and SI 1 and SI 2 are the corresponding signal intensities at each respective TE. Values for statistical analysis were capped at 250 ms to minimize measurement error, 23 as has been previously performed 22 …”
Section: Methodsmentioning
confidence: 99%
“…Although acquiring an additional, later echo image may aid in differentiating these subjects, it would also increase scan time, thereby limiting clinical feasibility. Even with this limitation, we sought to minimize the quantitative error to less than 10% due to the dual-echo acquisition by capping the calculated T2 values at 250 ms [3] and were able to assess the characteristics of the fluid reactions. In addition to more echo images, future investigations may benefit by accounting for subject-dependent T2 values by incorporating a normalization factor between affected and unaffected ROIs as is done in the setting of cartilage repair techniques [12].…”
Section: Discussionmentioning
confidence: 99%
“…where TE 1 and TE 2 are the user-defined first and second echo times, respectively, and SI 1 and SI 2 are the corresponding signal intensities for each echo time. Acknowledging that our echo times of 9 and 50 ms may be insufficient to fully characterize long T2 species in a synovial reaction, a numerical simulation was performed [3] to determine the effect of long T2 values and image noise when using these echo times in calculating T2. The simulation found that our echo times produced more than 10% error for T2 greater than 250 ms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation